Pinprick hypo- and hyperalgesia in diabetic rats: Can diet content affect experimental outcome?. (23rd April 2018) - Yadlapalli, Jai Shankar K.; Dogra, Navdeep; Walbaum, Anqi W.; Prather, Paul L.; Crooks, Peter A.; Dobretsov, Maxim
Highlights: Pinprick pain threshold was studied in a rat model of diabetes. Diabetic animals developed either pinprick hypoalgesia or pinprick hyperalgesia. The pain phenotype switch coincided with a change in diet content at a supplier animal facility. Diet consumed from childhood may modify progression of disease into adulthood. Abstract: Existing literature concerning the effect of experimentally-induced diabetes on pain thresholds in rodent models remains controversial. In this work, we describe a phenotypical switch from streptozotocin-induced pinprick hypoalgesia to hyperalgesia observed in the same laboratory, in the same strain of rats, obtained from the same vendor, and measured by the same technique carried out by the investigators. This switch was observed around January 2015, at the time when there was a change in the diet of rats at the Radley North Carolina Charles River facility. These data support the contention that diet may significantly modify disease progression, including progression of signs of diabetic neuropathy.